Muito prazer, anfitrião! (Nuntius Antiquus, 2011)
An approach to the theme of pleasure could not beavoided in Plautus’ Amphitruo, inasmuch as the prologue states(104 f.) that the great Jupiter spares no effort to get the women hedesires. Notwithstanding, Plautine craftsmanship disguises the themein this play with irony, ambiguity and euphemism. It’s a curious fact,for instance, that four out of the seven times the word uoluptas occursin the play are within the song (633-653) of the (self proclaimed)virtuous Alcmena, a passage whose value as a serious testimony, or asparody of lyric, is disputed. The dimension assumed by the topic ofpleasure in this comedy (as well as its contribution to the generationof poetic effects, the humorous ones among them) is the subjectmatterof this paper.